P212 Do you know who the male sex workers are in your cohort?. (18th May 2015) - Stockwell, Sarah; Dean, Gillian; Tweed, Marc; Boyt, Tom
Abstract : Background/introduction: Pro(TECT) is a bespoke service for male sex workers (MSW) launched by THT in June 2014. The service provides MSW with point of care HIV tests, STI and blood borne virus screening, as well as motivational interviewing, harm reduction and signposting to local SH services. Aim(s)/objectives: To describe the sexual health of MSW engaging with the local GU clinic. Methods: The notes of the Pro(TECT) clients who attended the local GU clinic were reviewed. Results: 15 MSW aged 20–57 years, attended the Pro(TECT) service from June to December 2014. 87% (13/15) had ever attended the GU clinic; 10 in the last 12-months. Only 3 revealed they were MSW. 39% (5/13) were HIV positive, of whom 3 had detectable viral loads (42, 000 to 307, 000 copies/ml). CD4 counts ranged from 6–698 × 10 6 /l. 85% were hepatitis B immune; 1 was hepatitis C co-infected (viral load 100, 4492 cp/ml). 33 STI screens were performed in the last 12-months, with an average of 3 screens/person. 39% (5/13) had an acute STI: 4 rectal, 3 pharyngeal, 1 urethral gonorrhoea; 2 rectal chlamydia; 1 latent (early/late) syphilis. PEP was used by 2 of the 5 HIV negative MSW a total of 5 times in 12-months. Discussion/conclusion: There is a high burden of STIs in this group and a significant risk of onward transmission. MSW may not disclose their work to health care professionals (HCP), even on direct questioning. Identification of MSW is fundamental in order to reduce risk and minimise harm. Pro(TECT) acts as a unique gateway into mainstream services, including advice to access PEP.